Early temperature records from a Norwegian coastal farm (1880–1930) - Nerheim, Ann Rigmor (Frontiers in Climate, 2025)
This paper presents new temperature data from a location on the northwest coast of Norway from the period 1880–1930. The data are based on diary notes of weekly temperature ranges. Maximum and minimum temperatures have been investigated, as well as weekly, monthly, and yearly average temperatures. The data indicate a decreasing yearly average temperature trend during the period from 1880 to 1930. Due to the origin of the data, the accuracy of the thermometer and readings are unknown.